Problematika zadolžene zapuščine - separatio bonorum - Žnidaršič Skubic, Viktorija (Podjetje in delo, 2016)
Indebtedness of states, economies, households and individuals is relatively large problem of today`s society: it is a global problem. With the increase of overindebted individuals the number of indebted deceased persons is also rising. In such circumstances the creditors of the deceased are increasingly using the institute of separation of heritage (separatio bonorum). In this way they want to protect their claims before possible intervention of the heir`s creditors. That is why the institute should be used above all by the creditors who are afraid that their claims, because of the heir`s overindebtedness, won`t be rewarded. Problem of actual practice is that the institute is used also in cases where there is no real need for using it. Different solutions in practice and in jurisprudence were accepted because of different understanding of relevant law. Because of that the topic is suitable for critical scientific assessment and also for some possible changes de lege ferenda.
Keywords: dediščina; dedno pravo; dolgovi; terjatve